Optimization Design of Shaper Mechanism Based on Nonlinear Programming Model. Issue 2 (October 2020) - Wu, Shibao; Chen, Guanxu; Ma, Jia; Gao, Jing
Abstract: Due to the lack of the optimization algorithm or model which could be used to optimize the complicated plane linkage mechanism (like a shaper mechanism), a nonlinear programming model which could solve this problem was proposed in this work, whose objective function was the minimum initial velocity of the cutting tool in the shaper mechanism, and the length of the linkages in the shaper mechanism was regarded as the constraint conditions. Subsequently, a typical shaper mechanism was chosen as the example to be optimized via this nonlinear programming model. The optimization results revealed that this model could acquire an appropriate optimization scheme effectively and the optimization scheme was reasonable.